1986
DOI: 10.1161/01.cir.74.3.626
|View full text |Cite
|
Sign up to set email alerts
|

The potential gradient field created by epicardial defibrillation electrodes in dogs.

Abstract: Knowledge of the potential gradient field created by defibrillation electrodes is important for the understanding and improvement of defibrillation. To obtain this knowledge by direct measurements, potentials were recorded from 60 epicardial, eight septal, and 36 right ventricular transmural electrodes in six open-chest dogs while 1 to 2 V shocks were given through defibrillation electrodes (1) on the right atrium and left ventricular apex (RA. V) and (2) on the right and left ventricles (RV.LV). The potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…2 C ), and found that the results are comparable. To be consistent with our previous study (13), we report only the interactivation intervals selected with peak-picking method. The interactivation interval is defined by the time difference between adjacent peaks.…”
Section: Discussionmentioning
confidence: 72%
“…2 C ), and found that the results are comparable. To be consistent with our previous study (13), we report only the interactivation intervals selected with peak-picking method. The interactivation interval is defined by the time difference between adjacent peaks.…”
Section: Discussionmentioning
confidence: 72%
“…10 This rapid firing may lead to multiple wavefronts on the heart at one time, which may degenerate back into VF. 11 While mapping studies have demonstrated that first myocardial activation emerges from the low field gradient region after near DFT shocks, 31,32 activation could originate in the conduction system in high gradient areas from rapidly firing Purkinje fibers and then spread to the low gradient areas. The rapid activation rate of the Purkinje fibers in the high gradient regions of the heart may be spreading through the specialized conduction system, but may not spread through the myocardial tissue because it is still refractory from the defibrillation shock.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent studies on the effect of short defibrillation pulses have demonstrated the importance of intramyocardial virtual electrodes caused by the coronary vasculature. 9 While membrane potential sources close to the extracellular electrodes are mostly produced by the macroscopic boundaries of the heart itself, 10 "far-field" virtual sources 11,12 most likely are caused by the bidomain nature 5,13 and the structural organization of myocardial tissue. 14,15 Theoretically, structural discontinuities may occur in both intra-and extracellular domains.…”
Section: Clinical Perspective On P 399mentioning
confidence: 99%